Analysis of prevalence, years lived with disability, and trends of anemia burden and main causes in China - Wang, Pengfei; Cheng, Xue; Guo, Qiya; He, Li; Ju, Lahong; Xu, Xiaoli; Gong, Weiyi; Li, Shujuan; Zhao, Liyun; Fang, Hongyun (Frontiers in Public Health, 2025)
BackgroundChina is facing a rapidly aging population. In 2020, the number of people aged 60 and above was 264 million, accounting for 18.7% of the total population. Therefore, addressing the health issues of older adults is of great importance. This study aimed to analyze trends of anemia burden and its underlying causes in older adults aged 60 and above.MethodsThree indicators were used to evaluate the disease burden of anemia: prevalence, Years Lived with Disability (YLDs), and Years Lived with Disability rate (YLD rate). Data on anemia prevalence were obtained from the 2002 Chinese Nutrition and Health Survey, the 2010–2013 Chinese Nutrition and Health Surveillance, and the 2015 China Adults Chronic Diseases and Nutrition Surveillance. A multi-stage stratified cluster random sampling method was adopted in these surveys. YLDs, YLD rate (per 100,000 population), and causes of anemia were sourced from the Global Burden of Disease 2021 (GBD 2021). The Cochran-Armitage trend test was used to test the trends between different ages, genders, and living areas.ResultsThe prevalence and YLD rate of anemia among older adults aged 60 and above exhibited a notable decreasing trend across various demographic factors. Anemia prevalence was higher in rural areas, western areas, and southern China. The YLD rate of females was higher than that of males, except for adults over 85. Both prevalence and YLD rates increased with age. Dietary iron deficiency was the leading cause of anemia.ConclusionWhile the disease burden of anemia has shown a decreasing trend, significant age, and regional disparities persist. Anemia among older adults, particularly in rural and western regions, remains a major health concern. Special attention is needed to address dietary iron deficiency as a key factor contributing to anemia.